(untitled) (Journal Of Educational and Psychological Researches, 2014)
Included a research problem , pointing to deficiencies and neglect in Arabic language teaching in primary and middle school , what makes sense to form your linguistic Bell ( Listening ) is missing , especially grammar, vocabulary endings . And stressed the importance of research that teaching students the Arabic language is the balance of the next life , and that any defect infects will demolish an important part of their structure and the fact that the theater is a form of human directcommunication , and it`s way is the word this helps students to develop some communication skills , and language the backbone of these skills ,1- The research sample was identified in all age children ( 6-12 ), which corresponds to the primary stage .2- The objectives have been identified as :3- 1- disclosure about the importance and role of theater in enriching and strengthening the linguistic wealth among primary school pupils .4- 2 theater ’s ability to amend the terms and vocabulary mistaken for rude and meaning among primary school pupils .It was the definition of each of the terms ( the language) and the concept of the theater (educational drama ) .Thetheoretical system took the framework and the objectives of the Children’s Theatre as well as the characteristics of children’s theater , and the general and special conditions that need to be taken into account when addressing the child’s theater :Previous studies have included :Each of the study : Alkakhan , Ameen and Lena Haniyeh (2009) study : Qurna , Ali Ahmed (2005) and Study: Lotfi , Mosa (2008) , and foreign studies : study (Rose, 2000)The third chapter dealt with methods of teaching Arabic to students in primary school and the optimum methods to promote it orally and expression through education play taking into account the different stages of growth , mental and emotional , in realistic phase, and free fantasy , adventure and heroism , and ideals .The fourth chapter deals with some of the most important conclusions that primary school pupils are more useful in language learning through drama . So the researcher recommended the need to employ this method in the teaching of the Arabic language , and work to achieve the project (linguistic immersion ) by making all conversations with children in classical Arabic .